2005
DOI: 10.1007/s00148-005-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Enclaves, language, and the location choice of migrants

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
150
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(154 citation statements)
references
References 20 publications
4
150
0
Order By: Relevance
“…Research has shown that adult members of ethnic minority groups rely heavily on their networks of co-ethnics to gain information about, for instance, the labor market in the host country and to make educational decisions for their children (Bauer et al 2005). It has been suggested that children of migrants adopt the same strategy and rely more heavily on sameethnic friends to gain school information and make educational decisions (Flashman 2014).…”
Section: Mixed Evidence For An Oppositional Culturementioning
confidence: 99%
“…Research has shown that adult members of ethnic minority groups rely heavily on their networks of co-ethnics to gain information about, for instance, the labor market in the host country and to make educational decisions for their children (Bauer et al 2005). It has been suggested that children of migrants adopt the same strategy and rely more heavily on sameethnic friends to gain school information and make educational decisions (Flashman 2014).…”
Section: Mixed Evidence For An Oppositional Culturementioning
confidence: 99%
“…These effects are likely to benefit low-skill migrants the most. In part this is due to them being more likely to be credit-constrained, but may be due also to the fact that ethnic enclaves provide services mainly to migrants with low skills in general and low levels of host-language fluency in particular (Borjas, 1999, Chiswick and Miller, 2005, Bauer et al, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In his study of Canada, Owusu (1999) underlines the importance of factors such as personal and cultural preferences, proximity to the ethnic group, the role of social identity, and the effects of actual or perceived discrimination in the housing market. Most studies on immigrants' location choices conducted in the United States argue that immigrants are attracted to large cities where other co-ethnic immigrants have settled before (Zavodny 1997;Jaeger 2000;Bauer et al 2002Bauer et al , 2005. With regard to the United States, Åslund (2005) concluded that the presence of earlier immigrant communities is the primary determinant of recent immigrants' location choices.…”
Section: Introductionmentioning
confidence: 99%